NILAI SOSIAL DAN FILOSOFIS TURUN DI WAY PADA UPACARA BEGAWI ADAT LAMPUNG DI TIYUH PANARAGAN - Nia, Intan; Nuni, Shela Lismawan (STKIP Pesisir Selatan, 2025)
Every culture is the result of a long process and represents the expression of the nation's noble values, rich with meaning and a perspective on the lives of its people. The lack of scientific research on culture in Indonesia can lead to its lack of recognition and even its gradual disappearance. This study explores the Turun di Way procession in the Begawi traditional ceremony of Lampung in Tiyuh Panaragan, which is rich in social and philosophical values. The procession functions not only as a ritual of purification before the awarding of traditional titles but also carries deep symbolic meanings, such as self-control and respect for ancestors. The research employed a qualitative method with in-depth interviews and observation. The findings reveal that Turun di Way embodies philosophical values such as Piil-Pusanggiri, Juluk-Adok, Nemui-Nyimah, Nengah-Nyappur, and Sakai Sambayan, which serve as moral guidance for the Lampung Pepadun community. Furthermore, the social values reflected in this tradition emphasize equality, solidarity, and mutual cooperation. Thus, the Begawi ceremony is not only a means of preserving cultural heritage but also strengthens the identity and character of Lampung society amidst the challenges of modernization.